Synthesis and Biological Properties of Ferrocenyl and Organic Methotrexate Derivatives - Ayine-Tora, D.M.; Rózga, K.; Puscion, E.; Hartinger, C.G.; Błauż, A. (ACS Omega, 2024)
Synthesis and biological activity of two series of modified side chain methotrexate (MTX) derivatives are presented, one with a ferrocenyl moiety inserted between the pteroyl and glutamate portions of the molecule and the other with glutamate substituted for short chain amino acids. Ferrocenyl derivatives of MTX turned out to be rather moderate inhibitors of dihydrofolate reductase (DHFR) although molecular modeling suggested more effective interactions between these compounds and the target enzyme. More interestingly, ferrocene-decorated MTX derivatives were able to impede the proliferation of four murine and human cell lines as well as their methotrexate-resistant counterparts, overcoming the multidrug resistance (MDR) barrier. They were also able to directly interact with Abcc1, an MDR protein. Of the amino acid pteroyl conjugates, the γ-aminobutyric acid derivative was an efficient inhibitor of DHFR but had no effect on cell proliferation in the concentration range studied while a taurine conjugate was a poor DHFR inhibitor but able to affect cell viability. We postulate that modification of the methotrexate side chain may be an efficient strategy to overcome efflux-dependent methotrexate resistance.
Research Article
Keywords: Biological Properties; Synthesis; Ferrocenyl; Organic Methotrexate Derivatives